Factores asociados a mayor ganancia de peso en neonatos pretérmino según características de la lactancia en el Hospital Regional de Loreto, 2019 - Ruiz Montenegro, Mariela Estefany (2023)
Preterm newborns account for 11% of live births worldwide, 60% of them in South Asia and sub-Saharan Africa. In low-income countries, 12% of newborns are born preterm, compared with 9% in higher-income countries. (17)In Peru, from 2010 to 2015 there was a decrease of 1% in terms of preterm birth rate (from 7.5% to 6.5%). In the department of Loreto, prematurity reached 8.1% of all births. (4) Weight gain in preterm infants is associated with many factors, among which the type and method of feeding received stand out. For this reason, this research project aims to identify the factors associated with greater weight gain in preterm infants according to the characteristics of breastfeeding. An observational, prospective, analytical, cross-sectional study was designed, the population to be studied will be preterm newborns hospitalized in the Intermediate and Intensive Care Service of the Loreto Regional Hospital during 2019, who meet the inclusion criteria. Relevant information will be collected in a previously elaborated form validated by a committee of experts. A database will be constructed from the information collected by the instrument in Microsoft Excel format and will be analyzed in Stata V15. For qualitative variables, frequencies and percentages will be determined, while for quantitative variables, measures of central tendency and dispersion will be calculated. The results to answer each specific objective will be presented in tables and graphs representing the analysis.